Effectiveness of a New Technique for Oral Cancer Screening - A Pilot Study - Audrey Madonna D'Cruz; Pushparaja Shetty; Urvashi Ashwin Shetty; Vinayak Kamath Bola; Vishnudas Dinesh Prabhu (Wolters Kluwer Medknow Publications, 2022)
Introduction: Screening programs with the use of specific diagnostic tools in asymptomatic patients are useful in identifying suspicious oral lesions and aid in the early diagnosis of oral cancer. The objective of the present study was to compare the oral rub and rinse technique with the conventional exfoliative cytology in the screening of oral malignant and potentially malignant diseases. Materials and Methods: An oral cancer screening program was conducted in the Dakshina Kannada district of Karnataka, India. The oral rub and rinse technique was performed on patients who had red/white lesions in the oral mucosa followed by the conventional exfoliative cytology. Scalpel biopsy was performed to confirm for presence or absence of malignancy in cases wherever indicated. Descriptive statistics (frequency and percentage) were used in the present study. Results: A total of 848 subjects were screened for oral cancer and precancer. About 112 participants had premalignant/malignant lesions and biopsy was performed on 30 subjects. Of these, 27.7% were Class I smears, 39.3% were Class II smears, 22.3% were Class III smears, 4.5% were Class IV smears, and 6.2% were unsatisfactory using the conventional technique, whereas the oral rub and rinse technique showed 26.8% Class I smears, 42.9% Class II smears, 19.6% Class III smears, 6.2% Class IV smears, 0.9% Class V smears, and 3.6% unsatisfactory. Conclusion: Although both the techniques could detect malignancy, the oral rub and rinse technique showed better cellular clarity and sample adequacy when compared to conventional exfoliative cytology, which makes it a practical tool in resource-challenged settings.